PENGARUH KOMITMEN ORGANISASI, SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi Pada Dinas Perindustrian, Perdagangan, Koperasi, dan UKM Kabupaten Dairi) - May Sartika Tarigan; Arthur Simanjuntak; Duma Rahel Situmorang (JURNAL MANAJEMEN, 2022)
This study aims to examine and analyze the effect of Organizational Commitment, Government Internal Control System (SPIP), and Human Resource Competence on the Application of Accrual-Based Government Accounting Standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency, in accordance with Government Regulation (PP) Number 71 of 2010 concerning Accrual-Based Government Accounting Standards which must be implemented comprehensively starting in 2015. This study uses a sampling method that is saturated sample, and data processing using multiple linear regression, F test and t test. This study uses primary data from questionnaires distributed to respondents. The results of this study indicate that partially organizational commitment and the government's internal control system (SPIP) have a positive and significant effect on the Application of Accrual-Based Government Accounting Standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency, while the competence of human resources has no effect on application of accrual-based accounting  standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency. Simultaneously Organizational Commitment, Government Internal Control System (SPIP), and Human Resource Competence have a positive and significant impact on the Implementation of Accrual-Based Government Accounting Standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency.